A Deixis Analysis in Taylor Swift’s Anti-Hero - Petaponi, Taftalia Surya; Duwila, Shanty; Astutik, Ari (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2024)
The objective of this research is to analyse the kinds of deixis and the types is more dominant used in Anti-Hero song lyrics. This research using qualitative method to analyse the kinds of deixis and the types is more dominant used in Anti-Hero song lyrics. The source of data taken from lyrics of Taylor Swift song lyrics Anti-Hero on the internet website genius.com. The data collected by: First, visiting and reading the music and lyrics platform to find out all the lyrics concerning with the object of the study and read all the lyrics from Anti-Hero song lyrics by Taylor Swift. Second, copy pasting the lyrics and putting all the lyrics in a folder that is formatted as a word documentation and saving it. The result of the analysis is that there are 4 types of deixis, namely, person, spatial, temporal, and social deixis in song lyrics from Anti-Hero and personal deixis is the most dominant used. The conclusion that the Anti-Hero song lyrics uses all different kinds of deixis, including person, spatial, time, and social deixis and person deixis is the most dominant form in the songs according to this study especially first-person deixis “I, me, my” that has 65 data.